(untitled) (Research, Society and Development, 2020)
Corn is a cereal widely consumed worldwide, presenting high production demand. The productivity of green corn is linked to water and nitrogen availability, and knowledge of the interaction between these factors is essential to achieve the best crop yields depending on the edaphoclimatic conditions of a given region. In the present work, we investigated the impact of different water depths (50%, 75%, 100%, 125% of the water replacement of evapotranspiration) and nitrogen doses (0, 70, 140, 210 kg N ha-1), besides the interaction between these two factors on the morphophysiology and production of green corn cv. Agroceres 1051 grown in cerrado of Goiás, Brazil. The different water depths and nitrogen doses did not affect physiological parameters such as net photosynthesis, stomatal conductance, transpiration and fluorescence. Regarding the morphological and production parameters, 125% water depth application increased the length of the ear without straw (CESP), the number of karyopses per row (NCF), stem diameter, green mass of the plant without ear (MVPSE) and the weight of the ear with straw. Fertilization treatment of 210 kg ha-1 of nitrogen increased the length of the ear with and without straw (CECP and CESP), NCF, MVPSE, as well as the diameter and weight of the ear with straw (DECP and PECP). There was a positive correlation between the leaf area (AF) and the productivity parameters. The effectiveness of nitrogen fertilization was limited by water availability for the parameters AF, plant height, number of leaves and length and width of the ear insertion leaf.